2018
DOI: 10.1007/s00421-018-4035-4
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in joint coordination remains unaffected by force and balance demands in young and old adults during simple sit-to-stand tasks

Abstract: Purpose We examined the possibility that old adults use flexibility in joint coordination as a compensatory mechanism for the age-related decline in muscle strength when performing the sit-to-stand (STS) task repeatedly under high force and balance demands. Method Young ( n = 14, 22.4 ± 2.1) and old ( n = 12, 70 ± 3.2) healthy adults performed repeated STSs under high and low force and balance demands. The balance de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 71 publications
0
10
1
Order By: Relevance
“…For instance, Latash (2010) has provided examples that in the middle stage of learning the UCM-like distribution might be more pronounced than when individuals are more proficient. Also, special populations demonstrate higher or equal UCM-like distribution than their healthy (or younger) peers (Black et al, 2007; Golenia et al, 2018; Greve et al, 2019). Furthermore, many of our experiments when analyzed for each individual do not show increased UCM and decreased ORT as would be expected (non-published results).…”
Section: Investigating Skill Acquisition (Change) As Searchmentioning
confidence: 98%
“…For instance, Latash (2010) has provided examples that in the middle stage of learning the UCM-like distribution might be more pronounced than when individuals are more proficient. Also, special populations demonstrate higher or equal UCM-like distribution than their healthy (or younger) peers (Black et al, 2007; Golenia et al, 2018; Greve et al, 2019). Furthermore, many of our experiments when analyzed for each individual do not show increased UCM and decreased ORT as would be expected (non-published results).…”
Section: Investigating Skill Acquisition (Change) As Searchmentioning
confidence: 98%
“…The older need balance to perform daily tasks such as walking quickly and sit-to-stand [27]. However, due to changes to the sensorimotor and neuromuscular system of the ankle and restricted ankle ROM, the older have decreased performance in static and dynamic postural, and these changes may increase the risk of falls [3,28].…”
Section: Discussionmentioning
confidence: 99%
“…The between-group differences in motor abundance in all three axes reduced as hopping frequency increased. This suggests that individuals with PFPS may have a "reserve capacity" to harness more motor abundance when required [10,24]. As hopping frequency increases, the body shifts intra-leg control of the vertical GRF from a strategy involving the hip-knee-ankle joints, to an independent ankle strategy [8].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that individuals with PFPS would exhibit a smaller index of motor abundance in the regulation of the vertical, AP, and ML GRFs compared to healthy individuals. Prior studies have shown a capacity for humans to harness greater motor abundance as task intensity increases [10] . Hence, we hypothesized that motor abundance between individuals with and without PFPS will become more similar at faster than slower hopping intensities.…”
Section: Introductionmentioning
confidence: 99%